The Comparison Analysis of Brand Association, Brand Awareness, Brand Loyalty and Perceived Quality of Two Top of Mind Camera Products - Revi Sesario; Nugroho Djati Satmoko; Errie Margery; Yusi Faizathul Octavia; Miska Irani Tarigan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this research is to compare the brand equity of Canon and Nikon cameras, which includes brand recognition, brand affinity, perceived quality, and brand loyalty. In this study, samples were drawn utilizing a non-probability sampling method and quota sampling strategy. A questionnaire with 27 statement items was utilized to gather data for the study, and 60 respondents were given it. Discriminant analysis has been used as the analytical technique in this work. The study's findings indicate that when the four aspects are taken together, there are variations in the brand equity of Canon and Nikon cameras. While the brand awareness factors for the two items are comparable, brand association variables, perceived quality, and brand loyalty are different.